Behavioral Economics of Education - Alexander K. Koch; Julia Nafziger; Helena Skyt Nielsen (Institute for the Study of Labor (IZA), 2014)
During the last decade knowledge about human behavior from psychology and sociology has enhanced the field of economics of education. By now research recognizes cognitive skills (as measured by achievement tests) and soft skills (personality traits not adequately measured by achievement tests) as equally important drivers of later economic outcomes, and skills are seen as multi-dimensional rather than one-dimensional. Explicitly accounting for soft skills often implies departing from the standard economic model by integrating concepts studied in behavioral and experimental economics, such as self-control, willingness to compete, intrinsic motivation, and self-confidence. We review how approaches from behavioral economics help our understanding of the complexity of educational investments and outcomes, and we discuss what insights can be gained from such concepts in the context of education.
Keywords: D03; I20; 330; non-cognitive skills; schooling; educational decision making; soft skills; behavioral economics